Early Home Visiting Delivery Model and Maternal and Child Mental Health at Primary School Age - Gabriella Conti; Sören Kliem; Malte Sandner (CESifo GmbH, 2024)
We study the impacts of a prenatal and infancy home visiting program targeting disadvantaged families on mental health outcomes, assessed through diagnostic interviews. The program significantly reduced the prevalence of mental health conditions for both mothers and children, measured at primary-school age, and broke the intergenerational association of these conditions. The impacts are predominantly associated with a particular delivery model, wherein a single home visitor interacts with the family, as opposed to a model involving two home visitors.
Keywords: I12; J21; J13; J16; 330; home visiting; mental health; diagnostic interviews